2005
DOI: 10.1161/01.hyp.0000189183.50301.5c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Sensitivity on Neural Cardiovascular Regulation in Essential Hypertension

Abstract: Abstract-Salt-sensitive hypertensive subjects, as defined by conventional categorical classification, exhibit alterations of autonomic cardiovascular control. The aim of our study was to explore whether, in hypertensive subjects, the degree of autonomic dysfunction and the level of salt sensitivity are correlated even when the latter is only mildly elevated and displays under-threshold values. Salt sensitivity of 34 essential hypertensive subjects was assessed on a continuous basis by the salt sensitivity inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…The effects of sodium diets we reported in normotensive individuals are similar to changes described in hypertensive patients 4, 5. Increased BRS, increased cardiac vagal index, and decreased HR and cardiac sympatho/vagal balance have been reported in hypertensive patients after a high‐salt diet, with these changes being blunted in those hypertensive patients with the more severe degree of sodium sensitivity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The effects of sodium diets we reported in normotensive individuals are similar to changes described in hypertensive patients 4, 5. Increased BRS, increased cardiac vagal index, and decreased HR and cardiac sympatho/vagal balance have been reported in hypertensive patients after a high‐salt diet, with these changes being blunted in those hypertensive patients with the more severe degree of sodium sensitivity.…”
Section: Discussionsupporting
confidence: 82%
“…Sodium loading/depletion maneuvers may unveil alterations in cardiovascular control associated with sodium sensitivity possibly involved in the increased rate of cardiovascular events. In this regard, while it has been shown that salt‐sensitive hypertensive patients respond to sodium loading with either a blunted sympathetic deactivation3 or an impaired cardiac parasympathetic activation,4, 5 limited evidence of an altered autonomic cardiovascular modulation is available in normotensive subjects.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study with hypertensive patients showed that high salt intake increased the HF and decreased the LF/HF components of HRV only in SI subjects (Minami, Kawano, Ishimitsu & Takishita, 1997). Moreover, SS patients with mild hypertension showed an impaired baroreceptor reflex after high salt intake (Coruzzi, et al, 2005), indicating a deficit in cardiac parasympathetic control. Structural changes in the cardiovascular system associated with the hypertensive adaptation could contribute to quantitative or qualitative differences from the HRV responses to salt observed in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Medical personnel performed a physical examination, a comprehensive medical history, electrocardiogram (EKG) and obtained blood and urine samples to ensure that the participants met the study entry criteria. Each qualifying subject participated in a 12-day experiment consisting of six days on a low sodium diet followed immediately by six days on a high sodium diet, similar to those in previous studies laboratories (Sullivan, Prewitt, Ratts, Josephs, & Connor 1988;Anderson et al, 1998;Coruzzi, et al, 2005). Participants were given low sodium-low potassium meals in insulated containers, and provided with dietary logs to record food intake to augment adherence to the diet.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the risk for the occurrence of cardiovascular events is Ͼ3-fold higher in saltsensitive than in salt-resistant hypertensive subjects. 3 In this issue of Hypertension, Coruzzi et al 4 show that in individuals with essential hypertension, even modest levels of salt sensitivity are associated with alterations in autonomic cardiovascular control. Their study strongly supports the idea that neurogenic mechanisms are involved in the pathophysiology of salt sensitivity in essential hypertension.…”
mentioning
confidence: 99%